Enhancing Early Childhood Mathematical Skills through Contextual Digital Game-Based Learning: Evidence from the BEKANTAN Intervention in Indonesia - Maghfirah, Febry; Kartika, Wilda Isna; Hasnur, Reyzia Anggriani; Azzahra, Vira; Pertiwi, Adharina (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
Early mathematical skills are crucial predictors of children's future success, yet they are often insufficiently stimulated during early childhood. This study investigates the effect of the digital game ``BEKANTAN''—an acronym for Bermain Matematika di Hutan Kalimantan (Playing Math in the Kalimantan Forest)—on the early math abilities of children aged 5–6 years in early childhood education. The study focuses on number knowledge, operations, geometry, algebra, measurement, and data analysis. This quantitative study used a pre-experimental One Group Pretest–Posttest Design. A total of 17 children were purposively selected from a population of 65, based on underdeveloped mathematical skills. Data were collected using a validated observation instrument and analyzed with SPSS 22, employing t-tests after normality and homogeneity tests. The results showed a significant increase in children's early math skills after using the ``BEKANTAN'' game, with a p-value of 0.001. This indicates the effectiveness of digital games in supporting foundational mathematical development in early learners. The study highlights the potential of integrating context-based digital learning tools into early childhood education to make abstract mathematical concepts more concrete and engaging. The findings are significant for educators and curriculum developers seeking innovative approaches to early childhood instruction. However, the study's limitations include its small sample size and lack of a control group, which may affect the generalizability of results. Future research should involve larger, randomized samples and explore the game's impact on other developmental domains. Additionally, expanding the content of digital games to include environmental and cultural elements—such as Kalimantan’s biodiversity—may enrich children's learning experiences while promoting local knowledge.